2018
DOI: 10.2134/agronj2017.06.0359
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Within‐Plant Variability of Cotton Fiber Length and Maturity

Abstract: A gronomy J our n al • Volume 110 , I ssue 1 • 2 018 47 D uring the past two decades, international demand for high cotton fi ber quality has increased because of the dominance of ring-spun yarn production. We hypothesized that minimizing the variability of cotton fi ber quality among fi bers within-bale could contribute to better spinning performance and yarn quality resulting in a better end-product with a lower cost of production. Th e variability in physical attributes among cotton fi bers within a bale ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Previous studies indicated that immature fibers break during processing [30][31][32][33]. In this study, it appears that the effect of Verticillium wilt results in poor development of secondary cell walls, rendering them weak and with a propensity to break during mechanical processing and create higher short fiber content.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies indicated that immature fibers break during processing [30][31][32][33]. In this study, it appears that the effect of Verticillium wilt results in poor development of secondary cell walls, rendering them weak and with a propensity to break during mechanical processing and create higher short fiber content.…”
Section: Discussionmentioning
confidence: 72%
“…Seedcotton was hand-picked from each boll in order to obtain F 1 seed. The seed cotton was ginned with a laboratory-scale roller gin (Dennis Manufacturer, Athens, TX), delinted with a research mechanical delinter at Texas A&M AgriLife Research & Extension Center, Lubbock TX, and planted by hand at the Texas Tech University research farm in Lubbock, Texas, on a loam soil with drip irrigation and following the recommendation for irrigated cotton production in the region (Ayele et al 2018). A total of 75 F 1 seeds for each of the nine crosses were planted in unreplicated 7.6-m long plots.…”
Section: Obtaining F 2 Seedmentioning
confidence: 99%
“…2). The seeds were planted on a loam soil with drip irrigation and following the recommendation for irrigated cotton production in the region (Ayele et al 2018). During the experiment, the accumulated rainfall was 272 mm and growing degree days (GDD 15.6 ) were 1308 units (Snowden et al 2013).…”
Section: Field Experimentsmentioning
confidence: 99%
“…Wang, et al, 2016, [ 12 ] observed when soil moisture decreased from approximately 60 to 45% of field capacity, yield reduction was doubled (from approximately 30 to 60%), and fiber quality, particularly fiber length and strength, was reduced. Periodic drought also increased within-plant variability of fiber maturity and fiber length of upland cotton cultivars, being more pronounced when boll setting was in the higher fruiting branches [ 13 ].…”
Section: Introductionmentioning
confidence: 99%